(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study aimed to demonstrate the impact of applying international standards for internal control and internal auditing in evaluating financial and administrative performance in the government sector. The problem of the study focused on the weakness of internal auditing in the government sector and the presence of obstacles that limit the ability of the General Administration of Internal Auditing to evaluate government financial performance. Three hypotheses were developed. Designing a questionnaire, and after collecting and analyzing data from the respondents, the study concluded that there is a statistically significant relationship between the application of standards of control and internal auditing and controlling administrative performance in the government sector at a significant level (0.000) and between the consistency of laws and regulations for internal auditing in increasing the effectiveness of internal auditing in evaluating and controlling And rationalizing the financial performance in government units at a significance level (0.000) and between training and qualifying auditors in accordance with international standards for control and internal auditing and evaluating administrative and financial performance in government units) at a significance level (0.000). The study recommended the need to regulate the affairs of the internal audit profession by establishing the professional association responsible for that. It also recommended There is a need to reduce the costs of applying professional performance standards so that they can be applied to confront the phenomenon of financial corruption.